Hubungan Kekerasan Selama Kehamilan Dengan Kelahiran Bayi Berat Lahir Rendah Di RSUD DR IBNU SOETOWO Baturaja Kabupaten OKU Tahun 2011 - Eni Folendra Rosa; Gunardi Pome; Marwan Baits (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2012)
Background: Low birth weight (LBW) is a risk factor which contributes to infant mortality during perinatal period and the greatest contributor to neonatal mortality in Indonesia. Some studies show that there is significant relationship between violence during pregnancy and LBW delivery. At District of Ogan Komering Ulu (OKU) there were 18 cases of violence domestic (2010) whereas the prevalence of LBW in 2010 was 7.1%. Objective: To identify the relationship between violence during pregnancy and LBW delivery at District of OKU. Method: This was an observational study which used unmatched case control study design and both quantitative and qualitative approaches. Subject of the study consisted of intervention group and control group at a comparison 1:2. Data analysis used univariable, bivariable with chi square (x), stratification and multivariable with logistic regression. Result: The result of bivariable analysis showed that the group of LBW had physical violence 3 times greater during pregnancy than the group with normal birth weight; and the group of mothers having LBW infants had psychological violence 2.5 times greater than the group with normal birth weight. Sexual violence, age, education and economic status statistically had no significant relationship with LBW; whereas frequency of antenatal care (ANC) had relationship with LBW delivery. The result of stratification analysis showed that the frequency of ANC was a modified effect and was not assumed as confounding variable. The result of multivariable analysis showed that the group of mothers with LBW infants had 2.5 times greater for violence during pregnancy than the group with normal birth weight infants. Conclusion: The group of mothers with LBW infants had more violence during pregnancy than the group with normal birth weight infants. Frequency of ANC, apart from violence during pregnancy, independently had significant relationship with the LBW delivery.